Adaptivna metoda merjenja statičnih karakteristik elektronskih komponent in njena realizacija z virtualnim instrumentom - Mohorko, Jože (Informacije MIDEM, 2001)
An approach to the computer-aided measurement of static characteristics is described. There are two basic criteria for choosing the number of measurement points: the speed of measurement performance and the continuity of the measured characteristic, which are contradictory. The approach is based on the adaptive method for choosing a limited set of measuring points with a uniform distribution along the characteristic, without the need for apriori knowledge about measured parts, limited by maximum permitted power, current and voltage. The approach is implemented as Virtual Instrument (VI) using LabView from national Instruments. The results of experimental of statical characteristics of different types of electronic elements, such as resistor zener diode, transistor and trystor, confirm the efficiency of the presented method even in the case of choosing a relatively small number of measurement points (10-15).
Keywords: elektronski elementi; napetost; preizkušanje; statične karakteristike; tok